Making Green Polymers Even Greener:Towards Sustainable Production of Polyhydroxyalkanoates from Agroindustrial By-Products - Gomez, José G. C.; Méndez, Beatriz S.; Nikel, Pablo I.; Pettinari, M. Julia; Prieto, María A.; Silva, Luiziana F. (IntechOpen, 2012)
None